Aquaporin-2 Promoter Is Synergistically Regulated by Nitric Oxide and Nuclear Factor of Activated T Cells. - Albertoni Borghese, Maria Florencia (2011)
Background/aims: We have previously shown that aquaporin-2 (AQP2) is down-regulated in the renal medulla of rats made hypertensive by chronic inhibition of nitric oxide synthase (NOS). It has been shown that AQP2 expression is regulated by the calcineurin/ nuclear factor of activated T cells (NFATc). Nitric oxide (NO) regulates the activity of NFATc via c-Jun-N-terminal kinase 2 (JNK2). Therefore, we hypothesized that increases in NO enhance NFATc-mediated up-regulation of AQP2 promoter activity. Methods: AQP2 mRNA and protein expression were detected in mouse renal papilla. AQP2-promoter-luciferase reporter and NFAT-luciferase reporter transfected MDCK cells were used to determine AQP2 promoter activity and NFATc activity, respectively. Cells were incubated with classic activators and inhibitors of NFATc and NO pathway. Results: Our results demonstrate that both Ca2+ and NO have a synergistic effect in increasing AQP2 mRNA and protein in mouse papilla, and in activating the AQP2 promoter in kidney-derived cells. In addition, NO enhances Ca2+-induced NFATc activation. The underlying mechanism involves increased NFATc nuclear import and decreased export via PKG-mediated inhibition of JNK1/2. Conclusions: This is the first study defining novel regulatory roles for NO and NFATc in the control of AQP2 expression, which is an important renal protein.